CAPACITY BUILDING OF LOCAL GOVERNMENT BUREAUCRACY IN IMPROVING PUBLIC SERVICE PERFORMANCE IN MUARA ENIM REGENCY, SOUTH SUMATRA PROVINCE - Abdul - Nadjib (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This research was based on two main purposes, namely to: (a) investigate the reasons behind the insuitability of public services implementation to public expectation and (b) find out the the model of local government capacity building in improving public service performanace in the context of Muara Enim Regency. Using a qualitative with participatory observation and in-depth interview with rich case informants, the results of this study were that the public service performance of the local government in Muara Enim was not in line with the public expectation due to the limited capacity of local government bureaucracy, leaders’ low political will, low public participation, and inhibiting endowement factors in providing the services. Bureaucratic capacity building included individual capacity, institutional capacity, and system capacities which was carried out through the preparation and implementation of the road map and grand design of local government bureaucracy capacity building. Findings arisen from this study was that in addition to building the capacity of the bureaucracy, public service improvement also required leaders’ political will, commmunity involvement and endowment factor in the administration of public services and in the policy formulation of local government bureaucracy capacity building. Keywords: Public service performance, Bureaucratic capacity building, Political will of leaders, Endowment factors, Community participation